2007
DOI: 10.1073/pnas.0608638104
|View full text |Cite
|
Sign up to set email alerts
|

Multiple reaction monitoring for robust quantitative proteomic analysis of cellular signaling networks

Abstract: Although recent developments in MS have enabled the identification and quantification of hundreds of phosphorylation sites from a given biological sample, phosphoproteome analysis by MS has been plagued by inconsistent reproducibility arising from automated selection of precursor ions for fragmentation, identification, and quantification. To address this challenge, we have developed a new MS-based strategy, based on multiple reaction monitoring of stable isotope-labeled peptides, that enables highly reproducib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
434
1
6

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 473 publications
(446 citation statements)
references
References 22 publications
4
434
1
6
Order By: Relevance
“…Darwanto and coworkers quantified H2B ubiquitination and H3 K79 methylation in the U937 human leukemia cell line and proposed a crosstalk regulatory mechanism between these two modifications 65. Wolf‐Yadlin and coworkers examined an EFGR network of 222 tyrosine phosphopeptides across seven time points following EGF stimulation of 184A1 HMEC cells, demonstrating excellent sensitivity, robust quantitation, and throughput 66. A useful case study and tutorial for targeted proteomics with enrichment is presented in Rardin and coworkers, in which they detail a method for measuring lysine acetylated peptides from mitochondria in mouse liver and targeted quantitation of a lysine acetylation site in succinate dehydrogenase A 67.…”
Section: Biology Applicationsmentioning
confidence: 99%
“…Darwanto and coworkers quantified H2B ubiquitination and H3 K79 methylation in the U937 human leukemia cell line and proposed a crosstalk regulatory mechanism between these two modifications 65. Wolf‐Yadlin and coworkers examined an EFGR network of 222 tyrosine phosphopeptides across seven time points following EGF stimulation of 184A1 HMEC cells, demonstrating excellent sensitivity, robust quantitation, and throughput 66. A useful case study and tutorial for targeted proteomics with enrichment is presented in Rardin and coworkers, in which they detail a method for measuring lysine acetylated peptides from mitochondria in mouse liver and targeted quantitation of a lysine acetylation site in succinate dehydrogenase A 67.…”
Section: Biology Applicationsmentioning
confidence: 99%
“…To omit the protein fractionation step and still maintain the same level of sensitivity we turned to SRM. SRM is associated with high sensitivity and specificity enabling quantification of the majority of the target proteins in 1D--LC--SRM--MS. 30 By pooling high, medium and low abundant proteins in separate transitions sets the sample load was optimized for the individual transitions sets. To reduce the number 8 of target proteins certain proteins were removed prior to the SRM analysis.…”
Section: Data Processingmentioning
confidence: 99%
“…In particular, we have recently shown that, integrating systems genetics data [19] with phospho-proteomics data and computational models of cellular kinase specificity [11], we could derive an integrative network model of JNK regulation in the fruit fly [12]. This network can now serve as a framework for future targeted proteomics studies [20,21] in cancer cells (in vitro and in vivo) to define how the network evolves and changes during cancer progression. We are now actively pursuing the integration of data from deep sequencing, functional genomics and extreme-throughput microscopy and mass spectrometry to perform network medicine and systems-level modelling of cancer metastasis [4,18].…”
Section: Integrative Network Biologymentioning
confidence: 99%
“…As we are moving towards multi-dimensional and integrative network models of cell behaviour, we expect that such models will be useful not just for determining network structures that can be targeted but also as predictive markers of disease emergence or progression [4,[22][23][24][25]. This will require robust quantitative network assays to become more widespread and userfriendly [21]. As mass-spectrometry proteomics continues to be a challenging technology to master, it is likely that network models established by quantitative mass spectrometry in the first instance will be easiest to implement in the clinic as affinity-based microarrays [4].…”
Section: Future Biomarkers -Network Signaturesmentioning
confidence: 99%